STRATEGI PEMASARAN METE SUPER WONOGIRI BERDASARKAN ANALISIS SWOT (Studi Kasus Sentra Jambu Mete di Kecamatan Jatisrono, Kabupaten Wonogiri) - Fajar Margyarto; Sri Hartono (JURNAL ILMIAH EDUNOMIKA, 2020)
The purposes of this research were to know: (1) the current condition of Mete Super Jatisrono based on SWOT analysis and the right strategy to develop Mete Super Jatisrono based on SWOT anaysis The method used in this research was a qualitative method with SWOT analysis as the main method. The researcher used documentation, field observation and quisioner as the data collection techniques. The researcher was able to determine the current condition of Mete Super Jatisrono by identity the internal and external factors. The results of this research were: S-O strategies was the most suitable strategies that can be used as main strategy to develop Mete Super Jatisrono. There is two main poin contained on S-O strategies: the first one is by doing online promotion by themself without hiring a social media expert, and the second one is by doing endorsement to promote Mete Super Jatisrono. Key Words: SWOT analysis, Mete Super Jatisrono